Role of GDP in the Sustainable Growth Era - Katarina Gajdosova (SocioEconomic Challenges, 2023)
While there is a correlation between economic growth and the increase in living standards, economic theory is evident in the purpose of the Gross Domestic Product (GDP) measurement. GDP measures only the production capacity and economic growth, not the nation's development, as often claimed by policymakers. Furthermore, as several studies show, by focusing on economic growth and neglecting the other two crucial systems, the ecosystem, and the social system, we will not be able to achieve economic growth in the future. Since the GDP was developed in 1937, it has faced criticism not only for its limitation related to its construction. Also, the concept of economic growth is currently being challenged and being replaced by the pursuit of sustainable development. Therefore, the role of GDP, as an economic growth indicator, in our economy needs to be clarified and re-assessed. The main aim of this paper is to investigate the usefulness of the GDP in the era of sustainable development. To achieve this, we investigated the historical development of various measures of economic growth, as well as the historical development of the GDP as an economic growth metric. Furthermore, we argue that the future of GDP should be in the multi-dimensional indicators, which are used to measure the sustainable development of a country, as opposed to a self-standing single-dimensional measure of economic growth. As a case study, we also construct two measures, based on Analytical Hierarchical Process (AHP) using the free online software 'SuperDecisions: our Simple three-dimensional index of the nation's growth and the enhanced holistic three-dimensional index - Holistic Nation's Growth Index. Using the AHP method, we showcase the difference between the countries' rankings if we consider only economic growth and if we focus on the country’s development more holistically. Our comparative study reveals that it is not enough to look only at three main systems, the economic, social, and ecosystem while assessing the countries’ development. It is necessary to also investigate and try to capture the relationships between those three main systems.